Enhancing Competitive Edge: The Impact of Marketing Strategy and Market Orientation on Vocational School Performance Through Strategic School Image Management - Rokhman Maulana; Titi Prihatin; Noor Hudallah (JUMPA : Jurnal Manajemen Pendidikan, 2024)
This study focuses on analyzing the influence of marketing strategies and market orientation on the marketing performance of private vocational high schools in Cirebon City, with school image as a mediating variable. The main purpose of this study is to understand how these two variables affect marketing performance directly and through the image of the school, as well as provide recommendations for school managers in improving competitiveness and marketing effectiveness. The research method used was quantitative with a survey approach, involving 100 respondents from various private vocational schools in Cirebon City. The data was analyzed using the Structural Equation Modeling (SEM) technique with the help of AMOS 24 software to test the causal relationship between the variables studied. The results of the study show that marketing strategies and market orientation have a significant influence on marketing performance, both directly and through the mediation of school image. The implications of this study emphasize the importance of managing school image as an integral part of a market-oriented marketing strategy, in order to improve school performance and competitiveness in the vocational education sector.